2021
DOI: 10.1007/s13311-020-00951-1
|View full text |Cite
|
Sign up to set email alerts
|

α6GABAA Receptor Positive Modulators Alleviate Migraine-like Grimaces in Mice via Compensating GABAergic Deficits in Trigeminal Ganglia

Abstract: Migraine is caused by hyperactivity of the trigeminovascular system, where trigeminal ganglia (TG) play an important role. This hyperactivity might originate from an underfunctional GABAergic system in TG. To investigate this possibility, we adapted a mouse model of migraine by inducing migraine-like grimaces in male mice via repeated injections of nitroglycerin (NTG, 10 mg/kg, i.p.), once every 2 days, for up to 5 sessions. Migraine-like facial pain scores were measured using the mouse grimace scale. Repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…The effective dose range (3-10 mg/kg, i.p.) of Compound 6 in suppressing tremor was similar to that in mouse models of schizophrenia (Chiou et al, 2018;Chiou et al, 2019) and migraine (Tzeng et al, 2020). At these doses, Compound 6 did not impair motor functions in rats (Knutson et al, 2018), nor display sedative (Wu and Chiou, 2016) or hypolocomotor activity (Chiou (which was not certified by peer review) is the author/funder.…”
Section: α6gabaar-selective Pq Compounds As a Novel Therapy For Essential Tremormentioning
confidence: 56%
See 1 more Smart Citation
“…The effective dose range (3-10 mg/kg, i.p.) of Compound 6 in suppressing tremor was similar to that in mouse models of schizophrenia (Chiou et al, 2018;Chiou et al, 2019) and migraine (Tzeng et al, 2020). At these doses, Compound 6 did not impair motor functions in rats (Knutson et al, 2018), nor display sedative (Wu and Chiou, 2016) or hypolocomotor activity (Chiou (which was not certified by peer review) is the author/funder.…”
Section: α6gabaar-selective Pq Compounds As a Novel Therapy For Essential Tremormentioning
confidence: 56%
“…We have previously demonstrated that Compound 6, one of the first α6GABAAR-selective PAMs identified (Knutson et al, 2018;Varagic et al, 2013), via acting at cerebellar α6GABAARs, ameliorated disrupted prepulse inhibition (PPI) of the startle response (Chiou et al, 2018), social withdrawal and cognitive impairment (Chiou et al, 2019) in animal models mimicking schizophrenia. By acting via α6GABAARs at trigeminal ganglia, it inhibited nociceptive activation of the trigeminovascular system and migraine-like grimaces in animal models of migraine (Fan et al, 2018;Tzeng et al, 2020). And, a deuterated Compound 6 analogue, DK-I-56-1, prevented and reduced trigeminal neuropathic pain in a rat model (Vasovic et al, 2019).…”
Section: α6gabaar-selective Pq Compounds As a Novel Therapy For Essential Tremormentioning
confidence: 99%
“…Transcript levels of enzymes (GAD65, GAD67) and transporters (VGAT) needed to synthesize and package GABA into vesicles are low according to transcriptomic studies (53,54). Yet functional proteins are detectable (15,23,55), as is tonic and induced GABA release (Fig. 7 and ( 15)).…”
Section: Discussionmentioning
confidence: 99%
“…All the study data were obtained from our previous study [ 22 ], where all animal experiments were approved by the Institutional Animal Care and Use Committee of National Taiwan University, College of Medicine, Taipei, Taiwan and were consistent with the national guidelines. Male mice (ICR strain, 8–10 weeks old, 30–35 g) were used in the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…We used a mouse migraine model induced by repeated and intermittent injections of NTG and a control group injected with saline [ 21 ]. The migraine-like painful facial expressions in mice were video-recorded and scored using the MGS [ 22 ]. Mouse facial images were classified as the NTG condition, saline condition, and preinjection condition.…”
Section: Introductionmentioning
confidence: 99%